Nonspecific protective factors in patients with early latent syphilis (report 1) - Zakharov , S.V.; Zakharov, V.K. (Medicni Perspektivi, 2021)
The objective of this work is to study nonspecific protective factors in patients with latent early syphilis. The results of the study are based on the data of a comprehensive examination before treatment of 142 patients with early latent syphilis and 20 patients of the comparison group. Methods of investigation: serological methods for the diagnosis of syphilis complex of serological reactions, enzyme-linked immunosorbent assay (IgM, IgG), Indirect immunofluorescence reaction (RIF) RIF-200, RIF-abs; determination of cytokines IL-2, IL-6, IL-10, TNFα and INFγ in blood serum by enzyme-linked immunosorbent assay; determination of the phenotype of lymphocytes (CD-receptors), the concentration of circulating immune complexes, phagocytic number, phagocytic index, Nitroblue tetrazolium test. In the blood serum of patients the concentration of IL-2, IL-6, IL-10 and TNFα, INFγ was significantly increased. The concentration of IL-10 and IL-6 was also significantly increased in patients with more than 1 year of infection. The most significant disorders of the parameters of the metabolic activity of neutrophils were found in patients with an infection of more than 1 year; an imbalance in the circulating immune complexes concentration was also established. Under the increasing duration of the infection, the concentration of CD16+ in the blood serum progressively decreases. The content of pro-inflammatory and anti-inflammatory cytokines in the blood serum of patients with early latent syphilis was significantly increased and depended on the timing of infection. This relationship was most pronounced for IL-6 and IL-10. In patients with early latent syphilis there is also an imbalance between CD25+ and late activation factor HLA-DR against the background of a progressive decrease in the number of CD16+ lymphocytes. A direct relationship was established between the time of infection and the number of NK-cells. The revealed disorders may be the consequence of significant disorders on the part of neutrophils and may be one of the factors of the latent course of syphilitic infection.